The numeric model of the properties of viscoelastic pavement layers made of asphalt concrete - Pożarycki, Andrzej; Górnaś, Przemysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Regardless of the complexity of performed analyses of pavement construction, the evidence for the high level of the real conditions rendering can be seen in the parameter values which need to be determined experimentally or through a reliable traceability of the parameters of a given model. By means of a detailed numeric analysis of a beam model, to which pure bending and periodic loading were applied, the authors determined the viscoelastic parameters of the sample HMA material. Next, the materials, defined in this way, were used for the construction of a pavement model. As a result of the juxtaposition of the calculation for the pavement model and the results of calculations performed with FWD, it was possible to confirm the convergence of the results on the level of accuracy accepted from the engineering perspective.